The used of recombinant plasmid DNA in GMO quantitative analysis of insect resistance maize targeted unapproved StarLink corn and approved Bt176 corn in food and feed sold commercially sold Malaysia - Khoo, Siew Ping; Cheah, Yoke Kqueen; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Genetically modified organisms (GMO) are increased remarkably from year to year and the estimated global area cultivated with genetically modified (GM) crops reached 125 million hectares in year 2008. However, insect resistance maize based on Bacillus thuringienses (Bt) is of the most cultivated GM crop in worldwide. Bacillus thuringiensis (Bt) is an aerobic, gram-positive bacterium that synthesize one or more Cry protein that are toxic to various types crop and forestry insects pests. To date, several cry genes have been introduced into GM plant to combat with various type of insect. Worldwide commercialization of GM crops has raised the customers’ concern about the Biosafety issues, and thus, many countries have implemented the labeling legislations for GM food and their derivatives. In this study, we introduced the quantitative analysis method based on the recombinant plasmid DNA as calibrators that can be used to determine the percentage of GMO content in various types of food and feed samples. Therefore, we have reported 7.5% (6/80) of the samples were contained StarLink maize and 1.25% (1/80) samples were contained Bt176 maize. Additionally, the percentage of GM content in each positive sample were further determined with the developed quantitative method. The percentage of the StarLink corns that present in the positive samples were varies from 0.09% to 2.53% and Bt176 corn that present in the positive sample was 16.90%. The present study demonstrated that the recombinant plasmid DNA that used in quantitative real-time method as good alternative quantitative analysis of GM content.